2021
DOI: 10.1371/journal.pone.0246902
|View full text |Cite
|
Sign up to set email alerts
|

Histological outcomes in HPV-screened elderly women in Denmark

Abstract: Introduction Danish women exit cervical cancer screening at age 65 years, but 23% of cervical cancer cases occur beyond this age. In addition, due to gradual implementation of cervical cancer screening, older women are underscreened by today´s standards. A one-time screening with HPV test was therefore offered to Danish women born before 1948. Methods Register based study reporting histology diagnoses and conizations in women found HPV positive in the one-time screening. Number and proportion of women with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
1
17
1
Order By: Relevance
“…Recently published results from a study in which Danish women older than 70 were invited for a single HPV screen showed that 4.1% of the women were HPV‐positive and 7.5% of those had CIN3+. 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently published results from a study in which Danish women older than 70 were invited for a single HPV screen showed that 4.1% of the women were HPV‐positive and 7.5% of those had CIN3+. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The last region to implement the new guidelines did so about 2 years after the first region (Appendix A , Figure A1), while one region (Capital) referred all HPV‐positive women to colposcopy, regardless of the infecting genotype. 17 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We emphasize that, although incident detection of HPV is often lower at older ages in well-screened populations, the proportion of newly HPV-positive women ultimately diagnosed with high-grade lesions or cancer is similar across all ages. 23 In fact, recent studies performing diagnostic excision in older women with persistent HPV infection in the absence of cytological abnormalities found a significant prevalence of underlying CIN2+, 24 suggesting that the risk of precancer in older women may be underestimated. The persistent risk of precancer and cancer across the lifespan described is particularly concerning given evidence that older women are screened less frequently, 26 may be more likely to actively decide not to screen, 26 and are more likely to perceive a lower risk of cervical cancer because of their current sexual activity.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%